Analyzing the biophysical inputs and outputs embodied in global commodity chains - the case of Israeli meat consumption - Shira Dickler (Journal of Natural Resources and Development, 2014)
The prevailing global livestock industry relies heavily on natural capital and is responsible for high emissions of greenhouse gases (GHG). In recent years, nations have begun to take more of an active role in measuring their resource inputs and GHG outputs for various products. However, up until now, most nations have been recording data for production, focusing on processes within their geographical boundaries. Some recent studies have suggested the need to also embrace a consumption-based approach. It follows that in an increasingly globalized interconnected world, to be able to generate a sustainable food policy, a full systems approach should be embraced. The case of Israeli meat consumption presents an interesting opportunity for analysis, as the country does not have sufficient resources or the climatic conditions needed to produce enough food to support its population. Therefore, Israel, like a growing number of other countries that are dependent on external resources, relies on imports to meet demand, displacing the environmental impact of meat consumption to other countries. This research utilizes a multi-regional consumption perspective, aiming to measure the carbon and land footprints demanded by Israeli cattle and chicken meat consumption, following both domestic production and imports of inputs and products. The results of this research show that the “virtual land” required for producing meat for consumption in Israel is equivalent to 62% of the geographical area of the country. Moreover, almost 80% of meat consumption is provided by locally produced chicken products but the ecological impact of this source is inconsequential compared to the beef supply chain; beef imports comprise only 13% of meat consumption in Israel but are responsible for 71% of the carbon footprint and 83% of the land footprint. The sources of Israel’s meat supply are currently excluded from environmental impact assessments of Israeli processes. However, they constitute a significant fraction of the system’s natural capital usage, so they must be included in a comprehensive assessment of Israel’s consumption habits. Only then can policy be created for a sustainable food system, and inter-regional sustainability be achieved.